2011
DOI: 10.1002/we.472
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics simulation of the aerodynamics of a high solidity, small‐scale vertical axis wind turbine

Abstract: A computational fluid dynamics simulation was performed for a small-scale, high solidity ( D 0:48) H-type Darrieus vertical axis wind turbine. Two-dimensional unsteady Reynolds-averaged Navier-Stokes equations were solved for the turbine numerical model, which has a large stationary domain and smaller rotating subdomain connected by a sliding mesh interface. The simulation results were first validated against steady-state airfoil data. The model was then used to solve for three rotating blades with constant am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 16 publications
1
47
0
Order By: Relevance
“…This was based on the review of relevant literature [5][6][7][8][9][10][11][12][13][14][15][16][17] that has shown that a 2D model is sufficient in revealing the factors that influence the performance and majority of flow physics that surround the VAWT. The contributions of blade end effects and blade-support arm junction effects are neglected but deemed acceptable since these can be considered as secondary.…”
Section: Numerical Model Of the Wind Tunnel Vawtmentioning
confidence: 99%
“…This was based on the review of relevant literature [5][6][7][8][9][10][11][12][13][14][15][16][17] that has shown that a 2D model is sufficient in revealing the factors that influence the performance and majority of flow physics that surround the VAWT. The contributions of blade end effects and blade-support arm junction effects are neglected but deemed acceptable since these can be considered as secondary.…”
Section: Numerical Model Of the Wind Tunnel Vawtmentioning
confidence: 99%
“…Then the tip vortex shedding from the upstream blade can affect the aerodynamic performance of the downstream blade. Meanwhile, the flow field around the wind turbine has a rather complex vortex structure and wind velocity distribution [8][9][10]. Therefore, any study on power performance of VAWTs needs to take into account the evolution of their flow field, especially the tip vortex effect.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the knowledge of the stalling process on VAWTs has been developed from lift and drag polars obtained from pitching aerofoil studies and simulations, Lee [8], [9], [10] and [11]. This is due to the difficulty of carrying out complex experiments on a rotating turbine.…”
Section: Nomenclature 1 Introductionmentioning
confidence: 99%